Association between C-reactive protein-albumin-lymphocyte index and stroke: an NHANES analysis (1999–2010) - Chen, Yizhou; Liu, Meifang; Zhang, Yi; Yang, Xiaolin; Yue, Mengqi; Chen, Xu; Wang, Haiqiang; Wang, Zirong; Yu, Haocheng; Shi, Jing (Frontiers in Neurology, 2025)
ObjectiveThis cross-sectional study is based on the NHANES (1999–2010) database and aims to explore the potential relationship between the CALLY index and stroke in the U.S. population.MethodsThis cross-sectional study utilized data from NHANES (1999–2010), including 17,511 American participants after data cleaning. Laboratory markers related to the CALLY index were obtained through standardized biological sample collection and analysis procedures performed by trained professionals. Stroke status was determined based on self-reported questionnaires. Various statistical methods were employed to examine the association between the CALLY index and stroke, as well as its predictive efficacy for stroke risk, including multivariable logistic regression, subgroup analysis, RCS analysis, and ROC analysis.ResultsAmong the 17,511 participants analyzed, our findings revealed a nonlinear L-shaped negative association between the CALLY index and stroke risk. In Model 3, a higher CALLY index was significantly associated with a lower stroke risk (OR: 0.99, 95% CI: 0.98–0.99, p = 0.045). Additionally, participants in the highest quartile (Q4) of the CALLY index had a 25% lower likelihood of stroke compared to those in the lowest quartile (Q1) (OR: 0.75, 95% CI: 0.58–0.97, p = 0.030). Furthermore, ROC analysis demonstrated that the CALLY index had superior predictive performance for stroke risk compared to the SIRI and SII indices.ConclusionA reduced CALLY index may be linked to a higher risk of stroke. Furthermore, the CALLY index demonstrates superior predictive performance compared to the SIRI and SII indices. The association between the CALLY index and stroke risk provides valuable insights for future stroke prevention and management strategies.